Rapid Allelic Discrimination by TaqMan PCR for the Detection of the Gilbert's Syndrome Marker UGT1A1*28 - Ehmer, Ursula (American Society for Investigative Pathology, 2008)
Gilbert's syndrome causes mild, unconjugated hyperbilirubinemia and is present in approximately 10% of the Caucasian population. The basis of the disorder is a 70% reduction in bilirubin glucuronidation catalyzed by the UDP-glucuronosyltransferase 1A1 (UGT1A1), which, in Caucasians, is the result of a homozygous TA insertion into the promoter region of the UGT1A1 gene (UGT1A1*28). Homozygous carriers of UGT1A1*28 as well as those with additional UGT1A variants can suffer from severe irinotecan toxicity or jaundice during treatment with the protease inhibitor atazanavir. UGT1A1*28 genotyping identifies patients at risk for drug toxicity and can increase drug safety by dose individualization. Rapid and facile UGT1A1*28 genotyping is therefore of great clinical importance. Two hundred ninety-one patients with suspected Gilbert's syndrome were genotyped using the TaqMan 5′nuclease assay with minor groove binder-non fluorescent quench probes; results were confirmed by direct sequencing. Ninety-six patients (33%) were homozygous for UGT1A1*28, which was verified by direct sequencing of a different PCR product showing 100% concordance with the TaqMan PCR results. We describe a novel UGT1A1*28 genotyping method that employs allelic discrimination by TaqMan PCR. This assay provides a rapid, high-throughput, and cost-effective method for Gilbert's syndrome genotyping, which is of value for pretreatment screening of potential irinotecan toxicity. The method utilizes a technological platform that is widely used in clinical practice and could therefore be easily adapted for routine clinical applications.